Reflective thinking in school: a systematic review - Anto Titus; Peter Varkey Muttungal (Institute of Advanced Engineering and Science, 2024)
Everything around us changes rapidly and to adapt to these constantly changing conditions and to understand the meaning of our life in the society in which we live, we must reflectively and consciously think about our actions in each given scenario. A school is a miniature form of society where learners are exposed to situations where they need to find solutions for every problem faced. No faultless solution and conclusions can be arrived at without a carefully employed reflective thinking process. In this context, the present study reviewed 19 intervention studies on reflective thinking in schools published between 2010 and 2021 and presents a brief summary. Various theories on reflective thinking, approach of educationists on reflective thinking of students and the relation between reflective thinking and students’ academic performance, are extensively analyzed. The findings of the study reveal that there are a few generally accepted theories of reflective thinking; reflection is a useful learning strategy and reflective thinking is an essential characteristic of academic excellence. This study recommends future research with a wider scope to accommodate more theoretical perspectives and wide-ranging databases.